The Influence of Contextual Aspects in Talent Development: Interaction Between Relative Age and Birthplace Effects in NBA-Drafted Players - Leite, Nuno; Arede, Jorge; Shang, Ximing; Calleja-González, Julio; Lorenzo, Alberto (Frontiers in Sports and Active Living, 2021)
The aims of this study were two-fold: (1) to inspect separately for the relative age and birthplace effects for players selected in the NBA Draft; (2) to explore the interaction among these factors and analyse this interaction in players’ career performance. The database was obtained from the official records of the players (n = 1738), who were selected during the annual editions of the NBA Draft from 1990 to 2019. The participants’ date of birth was analysed according to the month of birth and divided into four quartiles. The place of birth was compared to the distribution of the general population’ places of birth based on different communities’ sizes. Chi-square analysis were used to determine if the relative age and birthplace of the players drafted differed in any systematic way from official census population distributions. Cluster analysis and standardized residuals were calculated to analyse the interaction among the contextual factors and the players’ career performance. The data revealed that early-born players (Q1 and Q2) were over-represented. Moreover, players born in smaller cities (<50,000) were over-represented. The interaction analysis revealed that the players born in the bigger communities relate mainly with relatively younger players, and clusters that correspond to players born in smaller communities integrated the relatively older players. No significant differences were found in the players' career performance. Understanding the interaction between relative age and birthplace effects, could help researchers and practitioners on how to design sports systems and practice approaches to help nurture the development of sports talent regardless of age-related issues or communities’ size.